The Effect of Teaching Strategies and Students’ Self-Efficacy on Students’ Achievement in Reading Comprehension - Saragi, Christina Natalina (Journal of English Teaching as a Foreign Language, 2015)
The aims of this research are to find out: 1) whether students taught by using Metacognitive strategy have higher achievement than students taught by using Strategic instruction model in reading comprehension., 2) whether students who have high self-efficacy have higher achievement than students who have low self-efficacy in reading comprehension achievement, and 3) if the interaction between teaching strategies and self-efficacy significantly affects reading comprehension achievement. The study was conducted in the third semester students of Universitas HKBP Nommensen. The population was more than 200 students and the samples taken were 80 students. This research applied factorial design 2 X 2 by using the instruments of collecting data; reading comprehension test and questionnaire. All data were analyzed by using Two Way of Analysis of Variance (ANOVA). The results showed that 1) There is a significant effect of teaching strategies on students reading comprehension achievement, 2) there is a significant effect of self-efficacy on students’ reading comprehension achievement, and 3) there is a significant interaction between teaching strategies and self-efficacy on students’ reading comprehension achievement.